2020
DOI: 10.1007/s10610-020-09457-0
|View full text |Cite
|
Sign up to set email alerts
|

The Victim as Policy Agent? Exploring a Single Case from Denmark

Abstract: Criminal policy processes often appear abstract and illusive, but sometimes a single criminal incident causes traceable policy impact. This article is about such an incident. A victim of a grave, violent assault published an opinion piece in a national newspaper, which sparked considerable public debate and policy actions. Some policy actions were new, and others had previously been proposed but repeatedly discarded. Based on an empirical study of the victim's opinion piece, the ensuing media debate, and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This media interest in turn attracted political interest with an opposition politician introducing a private members Bill on parole (Jim O'Callaghan, Select Committee on Justice and Equality, May 24, 2017). While Irish research on the impact of the media on penal policymaking is scarce, this conclusion is consistent with international evidence; for instance, Asmussen et al (2022) showed that policy narratives, particularly those attracting media coverage, can capture the attention of macro-level actors, leading them to take action at the meso-level to bring about policy change. Ordinarily, bills tabled by a member of the opposition do not make progress through parliament but on account of a confidence and supply political arrangement which was in operation at the time, as well as cross-party support, the Bill became an Act (Griffin, 2020).…”
Section: Macro-level Influencessupporting
confidence: 70%
“…This media interest in turn attracted political interest with an opposition politician introducing a private members Bill on parole (Jim O'Callaghan, Select Committee on Justice and Equality, May 24, 2017). While Irish research on the impact of the media on penal policymaking is scarce, this conclusion is consistent with international evidence; for instance, Asmussen et al (2022) showed that policy narratives, particularly those attracting media coverage, can capture the attention of macro-level actors, leading them to take action at the meso-level to bring about policy change. Ordinarily, bills tabled by a member of the opposition do not make progress through parliament but on account of a confidence and supply political arrangement which was in operation at the time, as well as cross-party support, the Bill became an Act (Griffin, 2020).…”
Section: Macro-level Influencessupporting
confidence: 70%
“…No body homicide cases are relatively rare in Australia (Ferguson & Pooley, 2019), yet NBNP policies were established across the nation in haste with little debate, consultation, or consideration of their proposed effectiveness. We argue that politicians used individual cases, and the emotiveness associated with them, to drive legislative agenda because this is an effective means of demonstrating their responsivity to the electorate and tough on crime approaches (Asmussen et al, 2020; Freiberg et al, 2018; Moffa et al, 2019; Walklate, 2012). Western Australian debates, for example, were framed around Hayley Dodd (Kagi, 2016) and in Queensland around Bruce Schuler, Elizabeth Kippen, and Timothy Pullen (Horn & Stevenson, 2017).…”
Section: Introductionmentioning
confidence: 99%